Strategic management : confrontation to transformation - Volberda, Henk W; Hollen, Rick; Pereira, Joana; Sidhu, Jatinder; Heij, Kevin (London, UK ; Thousand Oaks, California : SAGE Publications Ltd, 2024)
"Change challenges leaders, managers and strategists, and demands that they confront their new realities. This book offers a fresh, reader-friendly, challenging and provocative perspective on strategic management, detailing the 'confront-sense-choose-transform' process stages, which begins with confronting business challenges and addressing several strategy tensions between theory and practice. In the continued quest for temporary advantage organizations need strategic capabilities to sense, choose and transform. The clear process stage model of strategic management and an action-oriented why-how structure help students and practitioners of strategy - from first year undergraduates to Executive MBA - to confront the new 'now' - fast, iterative and innovative. With each chapter dedicated to up-to-date theories of strategic management and specific practices from businesses around the world, illustrations and sets of activities that trigger the senses with rich supporting materials, this book will help grow readers' knowledge and experience of developing and implementing strategy in the real world"--
In the quest for competitive advantage, navigating change can be daunting. Following a unique, four-part structure focussing on and confronting strategic issues, sensing opportunities and threats choosing strategies and transforming organizations, this essential textbook offers a fresh and provocative perspective on strategic management.
Chapter 1 Introduction to Strategic Management Part I Confront Chapter 2 Direction, Purpose and Sustainability Chapter 3 Stakeholders and Corporate Governance Chapter 4 Competitive Rivalry and Nonmarket Forces Chapter 5 Emerging Technologies Diagnostic A: Confrontrix Part II Sense Chapter 6 Industry and Product-Market Analysis Chapter 7 Customer Analysis Chapter 8 Resources, Routines, Capabilities and Competencies Chapter 9 Ecosystems and Platforms Diagnostic B: iSense Part III Choose Chapter 10 Business-level Strategy Chapter 11 Diversification and Internationalization Chapter 12 Corporate-level Strategy Chapter 13 Network-level Strategy Diagnostic C: Choose Well Part IV Transform Chapter 14 Reconfiguration and Restructuring Chapter 15 Strategic Entrepreneurship Chapter 16 Business Model Innovation Chapter 17 Strategic Renewal Diagnostic D: Transformax
Includes bibliographical references and index.
CBA
In English
Keywords: Business and Management; Business planning; Strategic planning